2003
DOI: 10.1016/j.cellbi.2003.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Sterol glucosyltransferases have different functional roles inPichia pastoris and Yarrowia lipolytica

Abstract: Mutants of the methanol-utilizing yeast Pichia pastoris and the alkane-utilizing yeast Yarrowia lipolytica defective in the orthologue of UGT51 (encoding sterol glucosyltransferase) were isolated and compared. These mutants do not contain the specific ergosterol derivate, ergosterol glucoside. We observed that the P. pastoris UGT51 gene is required for pexophagy, the process by which peroxisomes containing methanol-metabolizing enzymes are selectively shipped to and degraded in the vacuole upon shifting methan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0
4

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 18 publications
3
38
0
4
Order By: Relevance
“…The Atg26 protein, encoding a uridine-diphosphateglucose:sterol glucosyltransferase, is required uniquely for both macro-and micropexophagy but not for starvationinduced macroautophagy in P. pastoris, or for pexophagy in Yarrowia lipolytica [44,61]. This protein has a pleckstrin homology (PH), GRAM (glucosyltransferases, Rab-like GTPase activators, and myotubularins) and a catalytic domain, all three of which are needed for micropexophagy.…”
Section: Micropexophagymentioning
confidence: 99%
“…The Atg26 protein, encoding a uridine-diphosphateglucose:sterol glucosyltransferase, is required uniquely for both macro-and micropexophagy but not for starvationinduced macroautophagy in P. pastoris, or for pexophagy in Yarrowia lipolytica [44,61]. This protein has a pleckstrin homology (PH), GRAM (glucosyltransferases, Rab-like GTPase activators, and myotubularins) and a catalytic domain, all three of which are needed for micropexophagy.…”
Section: Micropexophagymentioning
confidence: 99%
“…4 However, in the alkane-utilizing yeast Yarrowia lipolytica, it is not required for pexophagy. 6 Because the S. cerevisiae Atg26 protein (ScAtg26) possesses all three, PH, GRAM, and UDPGT, domains, which share significant sequence identities, 46%, 43.3% and 62.5% respectively, with those in PpAtg26, we were interested to know whether the ScAtg26 function was conserved. In this study, we determined the involvement of ScAtg26 in the Cvt pathway, macroautophagy and pexophagy.…”
Section: Introductionmentioning
confidence: 99%
“…They also showed that GlcSte accumulates in one strain of P. pastoris in response to heat or ethanol shock, in contrast to GlcCer, which appears to be constitutively expressed. The evidence suggests that GlcSte is not essential for viability, although UGT51p-catalyzed biosynthesis of GlcSte was recently shown to be required for oxidative metabolism of small molecules, such as methanol or alkanes, by some fungi (36,37).…”
Section: Discussionmentioning
confidence: 99%